2004
DOI: 10.1111/j.1944-9720.2004.tb02172.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Web‐Based Learning on Struggling EFL College Writers

Abstract: This study aimed at finding out whether there were significant differences in achievement between English‐as‐a‐foreign‐language (EFL) freshman students exposed to traditional in‐class writing instruction depending on the textbook only, and those exposed to a combination of traditional in‐class instruction and Web‐based instruction in writing. All students were pretested before instruction and studied the same writing textbook for 12 weeks. In addition, the experimental group of students received online instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 8 publications
5
25
0
Order By: Relevance
“…Cooperative group learning (Ghaith, 2003) and the use of technology (Al-Jarf, 2004;Ramachaudran, 2004) shift the focus from teacher controlled classrooms to student centered ones. Udvari-Solner (1996) argues for teaching strategies that extend further than delivering instruction to include content that is relevant to the student's lives; Udvari-Solner, Villa, and Thousand (2005) stipulate corrective feedback as part of teaching strategies and designing a teaching-learning process that can promote meaningful participation for all students within the classroom.…”
Section: Impact Of Teaching Strategies On Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperative group learning (Ghaith, 2003) and the use of technology (Al-Jarf, 2004;Ramachaudran, 2004) shift the focus from teacher controlled classrooms to student centered ones. Udvari-Solner (1996) argues for teaching strategies that extend further than delivering instruction to include content that is relevant to the student's lives; Udvari-Solner, Villa, and Thousand (2005) stipulate corrective feedback as part of teaching strategies and designing a teaching-learning process that can promote meaningful participation for all students within the classroom.…”
Section: Impact Of Teaching Strategies On Motivationmentioning
confidence: 99%
“…It should reorganize them with appropriate emphasis on the language skills. Also, at the same time workshops on topics such as multiple intelligences (Gardner, 1985;Gardner et al, 2004), catering for students' learning styles (Cortazzi & Jin, 1999), differentiating instruction (Tomlinson, 1995a;1995b); teaching and integrating all language skills; using technology in the language classes (Al-Jarf, 2004;Ramachaudran, 2004); and teaching language across the curriculum (Lavelle & Zuercher, 2001) would greatly, in the opinion of the authors, instill a positive attitude in the teachers and in so doing motivate the learners who will also have a change of attitude and self (Csizer & Dornyei, 2005a, b;Dornyei, 2010b;Gardner, 1983Gardner, , 1985Gardner et al 2004). …”
Section: Reflections and Implicationsmentioning
confidence: 99%
“…The scanty research that is available in the EFL or ESL context has come to conflicting results. On the positive side, we find studies that confirmed the superiority of WAI over TI in English writing performance (Al-Jarf, 2004b;Chuo, 2007;Kargozari & Hamed, 2010;Liou, 1997), English reading comprehension (Dreyer & Nel, 2003;Pan & Huang, 2009;Tanyeli, 2008) and English speaking (Chiu, Liou & Yeh, 2007). On the downside, there are studies that detected no significant differences in learning performance between online students and traditional classroom students (Lin, 2007;Liu, 2007;Shiu, 2002).…”
Section: Introductionmentioning
confidence: 81%
“…Online discussions increase their opportunities to exchange ideas with and learn from their native-English-speaking classmates (Al-Jarf, 2004;Belz & Kinginger, 2002;Gonzalez-Bueno, 1998). Thus, students who ordinarily would not participate in a classroom discussion "are able to give themselves a voice" (Al-Shalchi, 2009, p. 105; see also Young, 2008) in online discussions.…”
mentioning
confidence: 98%